APD Analisis Faktor Kepatuhan Penggunaan Alat Pelindung Diri (APD) Pada Petugas Laboratorium Di Kota Palopo Tahun 2024 - Tevri, Paula; Ilyas, Muh.; Saenuddin, Sudirman; Zamli, Zamli (PT.Mantaya Idea Batara, 2025)
Laboratories are among the units most vulnerable to work-related accidents and occupational diseases. Despite this, adherence to the use of PPE (personal protective equipment ) in laboratories remains very low. This study aims to investigate the factors influencing PPE